Strategi Penanganan Illegal Fishing oleh Kapolairud Baharkam di Laut Natuna Utara untuk Memperkuat Keamanan Nasional - Marsdianto, Marsdianto; Winarna, Agus; G. Andjioe, Bonifasius (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
Illegal fishing in the North Natuna Sea is a serious threat to Indonesia, both in terms of economy and state sovereignty. Disputed waters, especially in Indonesia's Exclusive Economic Zone (EEZ), are often targeted by foreign vessels with various modus operandi, such as identity forgery and detection evasion. The purpose of this study is to analyze the strategy for handling illegal fishing implemented by the Baharkam Police Chief in the North Natuna Sea to maintain national security. The research method used is qualitative descriptive with SWOT analysis. SWOT analysis is applied to evaluate the strengths, weaknesses, opportunities, and threats faced in handling illegal fishing in the region. The results of the study show that an effective strategy requires the integration of advanced technologies such as radar, thermal sensors, and ship tracking systems (VTMS), as well as strong national policy support. The Baharkam Police Chief also benefits from new technologies such as Sat-AIS and maritime drones, which play an important role in maritime surveillance. Comprehensive personnel training and the development of ships and patrol aircraft are important elements in strengthening the operational capabilities of the Kapolairud in dealing with illegal fishing and defending the sovereignty of Indonesian waters.